ANALISIS TERHADAP PENERAPAN DELIK UNSUR PEMERKOSAAN ANAK PADA PUTUSAN NOMOR : 11/PID.SUS/2021/PN/LRT - Fitrah Syaikhah Mosa Basa; Hery Firmansyah (Jurnal Hukum Adigama, 2022)
A child is a human being under the age of eighteen who is considered unable to distinguish between goodand bad deeds. So that a child protection law is formed which specifically regulates how a child isprotected by his rights and obligations before becoming a person who is considered capable as a legalsubject. From these regulations, children are also protected from sexual crimes committed by force andthreats of violence, but children are also protected from seduction or committing a series of lies so thatchildren can become a place to release someone's sexual desires. Therefore, there are rules that alsoregulate persuasion, deception, or a series of lies that have been regulated in the Child Protection Law, sothat if such an incident occurs, it must be prosecuted with an appropriate article between the act and theelements in it. article.This regulation is also one way to provide justice between victims and perpetrators ofcrimes.